Héctor Labat Moles, Le capitalisme dominé par la finance après le « shadow banking » : Implications analytiques, d’instabilité financière et macroéconomiques - Héctor Labat Moles (Revue de la Régulation)
The term "shadow banking" spread after the global financial crisis despite lacking any consensual definition. Heterodox authors adopted it without a comprehensive evaluation of its implications. This dissertation aims at reassessing the analysis of shadow banking within the heterodox tradition of finance-dominated capitalism macroeconomics from three angles: conceptual, analytical and empirical. First, the dissertation revisits shadow banking literature showing that "shadow banking" is a polysemic and polymorph term due to its competing uses as both a theory fix and a regulatory perimeter. Second, the dissertation exposes the inconvenience of shadow banking as an analytical category due to its polysemy, its political use and its inconsistency with heterodox theory, putting forward a conceptual reframing. Finally, the dissertation assesses empirically the macroeconomic implications of shadow banking studying the case of Spain (1998-2019) with the supermultiplier demand-led growth-decomposition methodology.